Gerakan Dakwah Ahmadiyah (Studi Kasus Jamaah Ahmadiyah Indonesia Desa Manis Lor Kecamatan Jalaksana Kabupaten Kuningan Jawa Barat) - Abdul Syukur (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2017)
In 2005, the Indonesian Ulama Council (MUI) issued a fatwa No. 11/ MUNAS/ VII/ 15/2005 on ‎the Ahmadiyah school. This fatwa established three important points which affirm the ‎apostasy of the Ahmadiyah school. Ahmadiyah misappropriates as it regards Mirza Ghulam ‎Ahmad as the last prophet, a very distorted view of the true teachings of Islam. In Manis Lor ‎Village, Jagalaksana, Kuningan district, there was a community of Ahmadiyah followers ‎named Jamaah Ahmadiyah Indonesia (JAI). This research was done by plunging directly into ‎Manis Lor Village. There were some interesting findings, among them was the fact that this ‎group had done the dawah in an organized manner by involving preacher (muballigh) who ‎voluntarily expres their readiness. Mubalig is also scholed, sworn and settled in an ‎environment where the Jemaah were located. The muballig also has the support of a ‎qualified financial. A muballig in charge of fostering and serving full-tme worshipers. On the ‎other hand, because mubalig only concentrates on nurturing and serving Jemaah, all the ‎burden of living expenses of mubalig and his family becomes dependent on the JAI ‎organization.‎